2011
DOI: 10.1159/000331700
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Reduces Augmentation Index but Not Aortic or Brachial Pulse Wave Velocity in Dialysis-Requiring Patients

Abstract: Background/Aims: Arterial stiffening characterizes the vasculature of end-stage renal disease (ESRD) patients and is a strong predictor of their cardiovascular morbidity and mortality. Previous studies evaluating the effect of hemodialysis on large artery elasticity gave contradictory results. This study aimed to investigate the impact of hemodialysis on arterial stiffness and wave reflections on chronic hemodialysis patients. Methods: A total of 51 stable ESRD patients on maintenance hemodialysis were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 50 publications
8
34
0
9
Order By: Relevance
“…The present study overcomes this limitation, showing a gradual interdialytic increase in wave reflections and a steady pattern of PWV during the whole 48-hour recording. These data are consistent with our previous observations that AIx was increased between the start and end of the 3-day and 2-day interdialytic intervals in contrast to aortic and brachial PWV, which remained constant (19,33).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study overcomes this limitation, showing a gradual interdialytic increase in wave reflections and a steady pattern of PWV during the whole 48-hour recording. These data are consistent with our previous observations that AIx was increased between the start and end of the 3-day and 2-day interdialytic intervals in contrast to aortic and brachial PWV, which remained constant (19,33).…”
Section: Discussionsupporting
confidence: 93%
“…Recordings in hemodialysis patients were obtained shortly before and after dialysis; these are subjected to biases related to the high variability of peridialytic BP and may not accurately reflect changes in arterial cushioning function during intra-and interdialytic periods (12,14). Previous studies evaluating changes in wave reflections and arterial stiffness during dialysis had this unavoidable limitation (17)(18)(19)(20). This may explain their largely contradictory results, with most studies showing reductions in augmentation index (AIx) during dialysis (17,20) and some also revealing a parallel decrease in pulse wave velocity (PWV) (18), whereas in others PWV remain unchanged (19) or even increased (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 In the same context, we have shown that although hemodialysis acutely reduces central SBP and AIx, PWV remained unchanged. 34 In this study, ambulatory PWV was the only vascular parameter independently predicting mortality, a finding probably related to the fact that PWV is the most direct estimate of arterial stiffness and that this analysis included the average 48-hour values of these parameters and not their variability, which in the case of AIx(75) could also be a factor affecting cardiovascular disease.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies on acute changes of arterial cushioning function in ESRD patients evaluated mostly the effects of a single HD procedure on arterial stiffness and/or wave reflections [14,15]. To this end, we have previously shown that during HD, pulse wave velocity (PWV) is not affected but augmentation index (AIx) and central BPs significantly decrease, possibly following reduction of peripheral wave reflections [16]. However, the effects of interdialytic interval on wave reflections were investigated only in one older study reporting changes in the AIx during a 2-day interval [17].…”
Section: Introductionmentioning
confidence: 99%